Does the DNA Protective Capacity of Lilium candidum Extract and its Components Depend on the Experimental Design? - Chankova, Stephka; Todorova, Teodora; Parvanova, Petya (Cutting Edge Research in Biology Vol. 3, 2023)
Here we have addressed two main questions: Whether the bioactivity of Lilium candidum extract and its main constituents - kaempferol and jatropham depend on the experimental design? How do kaempferol and jatropham as constituents of Lilium candidum total extract contribute to its bioactivity? These questions have defined our main objectives to clarify: 1) the contribution of experimental design to the DNA protective potential of Lilium candidum extract and its main constituents kaempferol and jatropham; 2) the contribution of kaempferol and jatropham to the DNA protective potential of Lilium candidum total extract. Chlamydomonas reinhardtii cell-wall-less strain CW15 from the Culture Collection of Algae and Protozoa (CCAP), Ambleside, UK, was used as a model object. To evaluate whether the experimental conditions can affect the bioactivity of Lilium candidum total extract and kaempferol and jatropham three experimental designs were performed: combined treatment; split treatment without the inter-treatment time; split treatment with 4-hour inter-treatment time. The kinetics of double-strand breaks (DSBs) repair was measured at the 2nd and 4th hour of the recovery time, and the magnitude of DSBs repair capacity was calculated. New evidence was provided that Lilium candidum total extract and its components – kaempferol and jatropham possess DNA protective capacity increasing the magnitude of cells' repair capacity. This effect was strongly dependent on the experimental design. Our results contribute to the concept that the bioactivity of plant extracts can be due to synergistic effects between individual components. Our finding that in some experimental conditions (design 2), Lilium candidum extract did not possess DNA protective potential against zeocin-induced DSBs, although two of its major constituents had such capacity, provoked new questions. They still remain open.